The importance of information in the preparation of feasibility study for construction development / Sharifah Nur Aina Syed Alwee…[et al.] - Syed Alwee, Sharifah Nur Aina; Salehudin, Nursazwaziha; Mohamed Sabli, Nor Azlinda; Isnaini Janipha, Nurul Afida; Maisham, Mysarah (Universiti Teknologi MARA, Kedah, 2018)
The planning of a project begins with envision of ideas, concepts and targets of the proposed construction development. Once set, all aspects of planning a development must be thoroughly evaluated during the preliminary stage of the Feasibility Study (FS). Matters that are related to technical, economic and financial aspects of the proposed development must be critically appraised in the FS. Without a well prepared FS, a development project can possibly fail due to issues such as inferior building quality, poor workmanship and cost overruns. For this reason, design consultants such as the architect, engineer and quantity Surveyor must always be aware so as to understand the importance of information needed in the preparation of FS. They should appreciate that the outcomes from an excellent FS could bring many good values for the construction project. The aim of this paper is to examine the importance of information required in the preparation of a FS and to explore the understanding amongst design consultants about its significance. Feedbacks obtained from the questionnaire surveys have shown that each consultant sets different priorities and purposes in identifying the crucial of data that they gathered during the FS. Though the main aim is to enhance the feasibility in terms of cost, quality and time demanded by the client, the research suggested that the views and suggestions made by consultants should not be ignored. In-depth investigations on economic, technical and financial analysis are the crucial factors to be considered so that at the final stage, the viability of a construction development would give good return on investment and other prospective values to the Client.